Critical Socio-Cultural Elements of the Intercultural Endeavour of English Teaching in Colombian Rural Areas - Sandra Ximena Bonilla; Ferney Cruz-Arcila (Universidad Nacional de Colombia, 2014)
This article reports a study done with five English language teachers in Colombian rural areas. Questionnaires and interviews were used to see how these teachers understand their professional practice considering the contextual features of their regional workplaces. Amongst the findings, we noticed that these teachers have to mediate between local and global tensions and also deal with socio-cultural matches and mismatches in their labours. It is hoped this work raises awareness of critical socio-cultural factors involved in the teaching of English in rural settings and of the complexity of its intercultural dimension.